Effect of compound dietary fiber of soybean hulls on the gel properties of myofibrillar protein and its mechanism in recombinant meat products - Zhang, Song-Shan; Duan, Jun-Ya; Zhang, Teng-Teng; Lv, Meng; Gao, Xiao-Guang (Frontiers in Nutrition, 2023)
Response surface methodology was used to determine the optimum ratio of rice husk dietary fiber, soybean hull dietary fiber and inulin as 1.40%, 1.42% and 3.24%. The effects of compound and single dietary fiber on water holding capacity, gel strength, secondary structure, rheological properties, chemical action force and microstructure of Myofibrillar Proteins (MP) gel were investigated. The application of composite dietary fiber significantly (P < 0.05) improved the gel strength, water holding capacity and storage modulus (G') of MP gel. Fourier transform infrared spectrum analysis shows that the addition of compound dietary fiber can make the gel structure more stable. The effect of dietary fiber complex on the chemical action of MP gel was further studied, and it was found that hydrophobic interaction and disulfide bond could promote the formation of compound gel. By comparing the microstructure of the MP gel with and without dietary fiber, the results showed that the MP gel with compound dietary fiber had smaller pores and stronger structure. Therefore, the rice hull dietary fiber, the soybean hull dietary fiber and the inulin are compounded and added into the low-fat recombinant meat product in a proper proportion, so that the quality characteristics and the nutritional value of the low-fat recombinant meat product can be effectively improved, the rice hull dietary fiber has the potential of being used as a fat substitute, and a theoretical basis is provided for the development of the functional meat product.